Pilot-Scale Removal of Trace Steroid Hormones and Pharmaceuticals and Personal Care Products from Municipal Wastewater Using a Heterogeneous Fenton’s Catalytic Process - George Tangyie Chi; John Churchley; Katherine D. Huddersman (International Journal of Chemical Engineering)
The pollution of water sources by endocrine disrupting compounds (EDCs) and pharmaceutical and personal care products (PPCPs) is a growing concern, as conventional municipal wastewater treatment systems are not capable of completely removing these contaminants. A continuous stir tank reactor incorporating a modified polyacrylonitrile (PAN) catalyst and dosed with hydrogen peroxide in a heterogeneous Fenton’s process was used at pilot scale to remove these compounds from wastewater that has undergone previous treatment via a conventional wastewater treatment system. The treatment system was effective at ambient temperature and at the natural pH of the wastewater. High levels of both natural and synthetic hormones (EDCs) and PPCPs were found in the effluent after biological treatment of the wastewater. The treatment system incorporating the modified PAN catalyst/H2O2 decomposed >90% of the EDCs and >40% of PPCPs using 200 mgL−1 H2O2, 3 hr residence time. The estrogenic potency EE2-EQ was removed by 82.77%, 91.36%, and 96.13% from three different wastewater treatment plants. BOD was completely removed (below detection limits); 30%–40% mineralisation was achieved and turbidity reduced by more than 68%. There was a <4% loss in iron content on the catalyst over the study period, suggesting negligible leaching of the catalyst.